STAD cooperative learning supported by question cards for figurative language learning: Implementation, impacts, and challenges in an Islamic elementary school - Sintia Nailus; Suci Herwani (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2026)
Figurative language instruction in Islamic elementary schools plays an important role in developing students’ language skills, yet many students still struggle to identify figurative language types and interpret figurative meanings. To address this problem, teachers implemented the Student Teams Achievement Division (STAD) cooperative learning model assisted by Question Cards as an alternative instructional strategy. This study aims to analyze the implementation of the STAD cooperative learning model, assisted by Question Cards, in figurative language learning, focusing on its implementation, impacts, and challenges. This study used a descriptive qualitative case study including one fourth-grade teacher and fourteen fourth-grade students. Data were collected through observations, semi-structured interviews, and documentation, then examined through the Miles and Huberman model. The findings revealed that the implementation of the STAD model integrated with Question Cards effectively improved students’ learning processes and outcomes. Students’ engagement and collaboration increased throughout the learning activities, with the average learning score improving from 61 to 84. The use of Question Cards supported students’ understanding of figurative language, strengthened peer interaction, and enhanced learning motivation. However, the implementation encountered several challenges, including limited instructional time, variations in students’ abilities, and the management of heterogeneous groups. The study shows that STAD, when supported by Question Cards, effectively improves students’ understanding of figurative language, participation, and learning outcomes, though effective time management and classroom organization are necessary. This study adds to the strengthening empirical evidence on integrating STAD and Question Cards in figurative language instruction while providing an alternative strategy to improve student participation and academic results in Islamic elementary schools.